Evaluation of Newborn Screening Practices and Interventions for Ocular Disorders Among Under-Five Children at Mzuzu Central Hospital, Malawi - Salem Rajab Alferjani (Surman Journal of Science and Technology, 2024)
This study investigates newborn ocular screening practices and intervention strategies for under-five children at Mzuzu Central Hospital, Malawi. A retrospective cross-sectional design was used, analyzing data from 400 children treated between 2019 and 2021. Findings revealed that 49.6% of the ocular disorders were serious and sight-threatening, with the highest prevalence among children aged 0–1 year. Time of intervention showed a stronger correlation with outcomes than type of intervention. Early screening and intervention significantly improved visual prognosis. The study highlights the need for institutionalized screening protocols to prevent avoidable visual impairments in early childhood.